Perception Of Primiparous Postpartum Mothers On The Challenges Of Exclusive Breastfeeding In Bukittinggi (HEALTH CARE: JURNAL KESEHATAN, 2026)
This study aims to analyze the relationship between midwife support and the perceptions of primiparous postpartum mothers regarding the challenges of exclusive breastfeeding in Bukittinggi in 2025. Exclusive breastfeeding coverage remains below the national target, particularly among first-time mothers who face various physical, psychological, and social challenges. This study used a quantitative method with a cross sectional design involving 45 respondents selected using consecutive sampling. Data were collected using a validated Likert-scale questionnaire and analyzed using univariate and bivariate analysis with the Spearman Rank test. The results showed that most respondents had low-level perceived challenges; however, a considerable proportion experienced high challenges, especially in psychosocial (42.2%) and social-environmental aspects (40.0%). Common challenges included anxiety, lack of confidence, and perceived insufficient breast milk. There was a significant relationship between midwife support and maternal perception (p < 0.05). It is concluded that midwife support plays an important role in shaping positive maternal perceptions and improving exclusive breastfeeding outcomes.